Recording and Evaluating the Tangible and Intangible Cultural Assets of a Place through a Multicriteria Decision-Making System - Eleni Linaki; Konstantinos Serraos (Heritage, 2020)
The starting point of this paper is the fact that multicriteria decision-making systems have not had the greatest impact on cultural studies, and few researchers have addressed this problem. The paper focuses on the analysis of the main object of an ongoing Doctoral thesis. More specifically, it examines the proposal of a new multicriteria evaluation based on a decision-making method. The paper intends to relate culture with multicriteria decision-making methods. This systematic review provides the direct analysis and assessment of the existing bibliographic references, and addresses a gap of knowledge in the intangible research field, identifying trends in the broader cultural heritage sector. The two basic principles of the paper are the recording and the evaluation of the cultural significance of the intangible and tangible heritage assets of a place. More specifically, the paper seeks to address a new scientific tool that initially records and—in the process—evaluates, using quantitative and qualitative criteria, specific cultural assets. Moreover, the paper outlines a new approach to the calibration—from optimal to worse—of the heritage of a place according to its significance. The purpose of the record and the evaluation is to create a ranking list of the most culturally significant tangible and intangible asset of places, in order to manage them. The design of the multicriteria method is based on a system that can be constantly updated diachronically, and can be fulfilled with new cultural assets and then re-evaluated. The explanation of the system is given through a step-by-step guide to the data analysis process, ensuring that the system has elements that are easy to access, to understand, and to use by each state actor (institution, individual, company, etc.).